Neuropsychological functioning in heart transplant candidates. Issue 1 (2nd January 2017) - Roman, Deborah D.; Holker, Erin G.; Missov, Emil; Colvin, Monica M.; Menk, Jeremiah
Abstract: Objective: This study provides age stratified neuropsychological test data for a large sample of heart transplant candidates. Patients with and without neurological co-morbidities were compared to better isolate the effects of congestive heart failure (CHF) on brain functioning.Method: Between 1988 and 2011, 956 patients (717 males, 239 females) with end-stage CHF and other life threatening cardiac diseases underwent neuropsychological assessment as a requirement of the heart transplant workup. Intellectual, memory, executive, language, attentional and psychomotor abilities were assessed, and standard cardiac measures were concurrently collected. Independent t -tests were used to compare subgroups with and without neurological co-morbidities on cardiac, neuropsychological and MMPI-2 measures. Chi-square tests were used for categorical items to compare demographic data between the two groups.Results: Significant cognitive impairments across all domains assessed were typical in all age groups. Neurological co-morbidities, such as CVA and cardiac arrest were common, with 28% of the sample having one or more condition. That subgroup scored lower on measures of processing speed, memory, and executive measures, but the pattern of deficits was similar for both groups and not explainable by depression. Depression prevalence per MMPI-2 findings was comparable to that of the general population.Conclusions: End stage heart disease/heart failure is associated with global, mild to moderate cognitive impairment, regardless of age or neurological co-morbidities. Contributing factors likely include cerebrovascular hypoperfusion, multiorgan failure, systemic co-morbidities, and lifestyle issues.